SPIRAL THEORY OF THE HUMAN BODY: THE POSITIVE AND NEGATIVE SPACE IN HUMAN EMBRYONIC DEVELOPMENT - N. Pirovski; I. Ivanova; S. Hamza (Trakia Journal of Sciences)
The accumulated amount of information about human morphology is enormous and this leads to a suitable environment for a new qualitative leap in the understanding of the human body. Material and Methods: Scientific publications available online. The methodology is: heuristic formation of the goal, systematic thinking, holistic approach, and comparison between the up-to-date embryology facts with the modern theories in physics and the traditional holistic philosophies of China. Aim: The purpose of this report is to validate STHB from an embryological point of view. Results: The embryonic period provides clear evidence for the spiral theory of the human body, demonstrating the center, its boundary, the equal importance of negative and positive structures, the primordial scale and the transition to different sub-scales, its short duration, and the clear transition to the next period of life. Conclusion: Most axioms of the STHB could be validated by human embryo development. As a disadvantage, one can consider the weak anthropological demonstration of the typical human characteristics that distinguish him from the animal world.